Transition from systems to commodity research at ILCA: Perspectives on cattle production studies 1988-92 - Coppock, D. Layne; Chigaru, P.R.N. (Tanzania Society of Animal Production, 1989)
Describes the major changes in institutional structure, philosophy and focus occured at ILCA on the livestock production systems in Africa; reviews the establishment of research priorities on which basis six research thrusts or areas of focus have been selected; examines in detail the primary objectives and the main obstacles of the Cattle Milk and Meat thrust, with particular reference to calf mortality, calving intervals, feeding packages, milk processing techniques, disease investigation and control, socioeconomic obstacles to milk and meat consumption, and to the production potential of cattle breeds and their crosses in different ecological zones of Africa.